Предмет: Алгебра,
автор: Qwerty677655
Решите пожалуйста только а)
Приложения:
Ответы
Автор ответа:
0
z1=-1+i√3; z2=3-3i
z=z1+z2= -1+i√3+3-3i=2+(√3-3)i
z=z1*z2= (-1+i√3)(3-3i)=-3+3√3i+3i+3√3=(3√3-3)+i(3+3√3)
z=z1/z2=(-1+i√3)/(3-3i)=(-1+i√3)(3+3i)/(3-3i)(3+3i)=
=-3+3√3i+3i+3√3/18=(3√3-3)/18+(3√3+3)i/18
z=z1+z2= -1+i√3+3-3i=2+(√3-3)i
z=z1*z2= (-1+i√3)(3-3i)=-3+3√3i+3i+3√3=(3√3-3)+i(3+3√3)
z=z1/z2=(-1+i√3)/(3-3i)=(-1+i√3)(3+3i)/(3-3i)(3+3i)=
=-3+3√3i+3i+3√3/18=(3√3-3)/18+(3√3+3)i/18
Похожие вопросы
Предмет: Физика,
автор: oksanafokina419
Предмет: Математика,
автор: mendybaevalisher7
Предмет: Биология,
автор: milasshkinna
Предмет: Литература,
автор: Аноним
Предмет: Геометрия,
автор: Mishanya9999